Serum selenoprotein P concentrations and cardiovascular disease: results from a large, prospective cohort study of older German adults - Cui, Zhixin; Schomburg, Lutz; Holleczek, Bernd; Hybsier, Sandra; Köhrle, Josef; Brenner, Hermann; Schöttker, Ben (Free radical biology and medicine, 2025)
Background - Studies on the association of selenoprotein P (SELENOP) with cardiovascular outcomes yielded inconsistent results. We assessed the association of SELENOP serum concentrations with cardiovascular disease (CVD), stroke and coronary heart disease (CHD) in CVD-free adults and the association with CVD mortality in CVD patients. - Methods - Serum SELENOP concentrations were measured at baseline and 5-year follow-up in 6600 CVD-free participants and 1729 CVD patients aged 50-74 years from the German ESTHER study. Multivariable Cox models were performed. - Results - During 17 years of follow-up, 1837 CVD-free participants developed CVD, of whom 675 had a stroke and 1153 were diagnosed with CHD, and 352 CVD patients died from CVD. In the multivariable Cox model, CVD-free participants in the lowest SELENOP quartile had a 1.5-fold higher stroke risk than those in the highest quartile (HR [95 %CI], 1.58 [1.17-2.12]). Associations with CVD incidence were only observed in patients with hypertension (HR [95 %CI], 1.21 [1.03-1.41]) or diabetes (HR [95 %CI], 1.36 [1.01-1.83]). No association was observed between SELENOP concentrations and CHD incidence. Furthermore, CVD patients in the lowest SELENOP quartile had an almost 2-fold increased CVD mortality compared to the rest (HR [95 %CI], 1.85 [1.31-2.60]). - Conclusions - Low serum SELENOP concentrations were associated with an increased risk of stroke in subjects free of CVD and with CVD mortality among CVD patients. The association of SELENOP concentrations with CVD incidence was restricted to patients with hypertension or diabetes. Well-designed trials are required to assess potential preventive effects of selenium supplementation.